El Castillo cave (Cantabria, Spain): Archeozoological comparison between the Mousterian occupation level (unit 20) and the "Aurignacien de transition de type El Castillo" (unit 18). (June 2020) - Luret, Mathieu; Burke, Ariane; Bernaldo de Quiros, Federico; Besse, Marie
Highlights: El Castillo is part of the cave system of Cantabria, a UNESCO world heritage site. Its stratigraphy documents the Middle to Upper Paleolithic transition. Archeozoology is used to define human subsistence strategies during this transition. Mousterian populations are non-specific in their subsistence strategy. Whilst Aurignacian populations specialise in red deer hunting as a nutrition source. Abstract: In Spain, the site of El Castillo is part of the emblematic cave system of Cantabria, famous for its cave art. They are registered as a World Heritage Site by UNESCO since 2008. This archaeological site is also important due its stratigraphic sequence, which spans several prehistoric occupation units and in particular the techno-complexes of the Middle to Upper Palaeolithic transition. These constitute the subject of this article. We carried out an archaeozoological / taphonomical analysis on the faunal skeletal remains of unit 20 (Mousterian) and unit 18 (Aurignacien de transition de type El Castillo), in order to study the evolution of subsistence strategies of the human populations between the end of the Middle Palaeolithic and the start of the Upper Palaeolithic, in the Iberian Peninsula. This research demonstrates that units 20 and 18 reflect differences in species acquisition. The humans of unit 18 targeted red deer specifically, whilst the Mousterian are less speciality and hunted red deer, horses, and bovines (auroch or bison). Level 18 shows a specialisation in deer acquisition, but it is worth noting that it is also the most important animal in level 20. Its prevalence in level 20 only appears lower because other species are present in greater proportions (horse, Bos/Bison).